Comparing the economic value of virtual water with volumetric and stress-weighted approaches: a case for the tea supply chain - Lowe, Benjamin H.; Oglethorpe, David R.; Choudhary, Sonal (Elsevier, 2020)
In this paper, we employ a new approach to assessing the impact and efficiency of virtual water use along the supply chain. This approach involves estimating the economic value of virtual water flows. A realistic tea supply chain case study is presented to test this new approach and compare it with alternative volumetric and stress-weighted methods. The case study is used to highlight the total value of the blue and grey water used to produce 1 tonne of tea as a finished good ($224). The case study also illustrates how variations in the relative unit value of water between geographies, in this case between multiple locations where crops are cultivated (India $0.08 m3, Indonesia $0.09 m3 and Kenya $0.27 m3), can be used to inform supply chain optimisation and allocative efficiency. Indeed, the case study suggests that taking into account the economic value of virtual water may provide differing prescriptions for the sustainable management of supply chains when compared to the traditional volumetric water footprint, and the stress-weighted water footprint used in LCA.
Keywords: Water footprint; Virtual water; Supply chain management; Stress-weighted water footprint; Economic value of water; Benefit transfer